Analisis Harga Dan Digital Marketing Terhadap Loyalitas Melalui Keputusan Berkunjung Dan Kepuasan Pada Pengunjung Rasamadu Heritage - Hanita Mega Yuliana; I Gusti Putu Diva Awatara (Excellent, 2026)
The purpose of this study is to determine and provide empirical evidence of the significance of the influence of Price and Digital Marketing on Loyalty through Visiting Decisions and Satisfaction among Rasamadu Heritage visitors. This research is quantitative in nature, with a sample of 100 Rasamadu Heritage customers. The sampling technique used is non-probability sampling using accidental sampling. Data analysis methods tested include validity testing, reliability testing, t-testing, F-testing, R2 testing, and path analysis testing. The results of the analysis show that: partially, price and digital marketing have a positive and significant effect on visit decisions. Price and digital marketing have a positive and significant effect on customer satisfaction. Price and customer satisfaction have a positive and significant effect on customer loyalty. Meanwhile, digital marketing has a positive but insignificant effect on customer loyalty. Visit decisions have a negative and insignificant effect on customer loyalty. The results of the Simultaneous Significance Test (F Test) of equation 3 show that together, the variables of price, digital marketing, visit decision, and customer satisfaction have a significant effect on customer loyalty at Rasamadu Heritage. The determination results show a total R2 value of 0.998, which means that Rasamadu Heritage customer loyalty is explained by the variables of price, digital marketing, visit decision, and customer satisfaction by 99.8%, and the remaining 0.2% is explained by other variables outside the research model, such as location and service quality.